A MODEL FOR PREDICTION OF RESOURCES AND ECONOMIC SUSTAINABILITY ON CHIRIMEN AGROINDUSTRY - Bambang Herry Purnomo, Machfud, Aji Hermawan dan Eko Sri Wiyono (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTIn recent years, the capture fishery agroindustry has been facing serious problems on various dimensions. Those problems will threat its sustainability in the future. This study aimed to design a model for prediction of resource and economic sustainability for chirimen agroindustry and developed policies to improve its sustainability. This model was developed by using dynamic system modeling and implemented on chirimen agroindustry at coastal area of Tuban, Lamongan, and Gresik. The result of simulation showed that the resource and economic sustainability indexes of chirimen agroindustries will not sustain in 2016. To improve those condition, synergetic policy that involved government and agroindustry was required. Government should regulate fishing effort, while agroindustry should establish some policies, i.e. 1) reduce production cost; 2) increase product differentiation; 3) improve human resource skill; and 4) increase volume of the semi finished good. The scenario could improve the sustainability index to be enough sustainable for both dimensions, resources and economic.Keywords: chirimen agroindustry, prediction model, sustainability,dynamic system modeling, policyscenario